2017
DOI: 10.1093/neuros/nyx156
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Safety and Cost-Effectiveness of Venous Thromboembolism Prophylaxis Strategies in Patients Undergoing Craniotomy for Brain Tumor

Abstract: Although MP+LMWH is frequently considered the optimal prophylaxis for VTE risk reduction, our model suggests that MP+UFH is the safest and most cost-effective measure to balance VTE and hemorrhage risks in brain tumor patients at lower risk of hemorrhage. MP+LMWH may be more effective for patients at higher risk of VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
1
19
0
3
Order By: Relevance
“…This is especially true in the US; in a contemporary review of VTE prophylaxis in neurosurgery, the authors state that IPC was used as the main means for mechanical VTE prophylaxis in all US centers that contributed data to the review. 2 However, in their conclusion they ultimately chose to recommend mechanical prophylaxis (along with unfractionated heparin) without further differentiation between IPC and compression stockings: as yet, there is no proven superiority of IPC over compression stockings in patients undergoing neurosurgery. 3 In the present study, such superiority has now been demonstrated by a controlled, prospective, and randomized single-center setup.…”
Section: Figmentioning
confidence: 99%
“…This is especially true in the US; in a contemporary review of VTE prophylaxis in neurosurgery, the authors state that IPC was used as the main means for mechanical VTE prophylaxis in all US centers that contributed data to the review. 2 However, in their conclusion they ultimately chose to recommend mechanical prophylaxis (along with unfractionated heparin) without further differentiation between IPC and compression stockings: as yet, there is no proven superiority of IPC over compression stockings in patients undergoing neurosurgery. 3 In the present study, such superiority has now been demonstrated by a controlled, prospective, and randomized single-center setup.…”
Section: Figmentioning
confidence: 99%
“…A lack of scientific evidence is primarily the cause of this variation in recommendations. Recent systematic reviews and meta-analyses of VTE prophylaxis in patients undergoing craniotomy for brain tumors have been performed [ 42 , 57 60 ]. These analyses have compared different VTE prophylaxis modalities, as well as their safety and cost effectiveness, but they do not thoroughly investigate the efficacy of prophylaxis over time to determine a recommended duration.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients may not need or benefit from continuing thromboprophylactic therapy beyond discharge. Algattas et al reviewed the safety and effectiveness of thromboprophylactic strategies and indicated that different regimens may have different efficacies depending on the patient’s VTE risk profile [ 57 ]. This highlights the importance of using the appropriate risk profile for optimizing postoperative management.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence rates of DVT and PE among neurosurgical patients are 0-34% and 0-3.8%, respectively. Brain tumors are correlated with the increased risk of VTE and, among patients with brain tumors, the incidence rates of DVT and PE have been reported to be 24-30% and 0-5%, respectively [2,[4][5][6][7][8][9][10]. Chemoprophylaxis with low-molecular-weight heparin (LMWH) has been found to be the most efficacious method for VTE prevention when compared with unfractionated heparin (UFH) and mechanical prophylaxis (MP).…”
Section: Introductionmentioning
confidence: 99%
“…Chemoprophylaxis with low-molecular-weight heparin (LMWH) has been found to be the most efficacious method for VTE prevention when compared with unfractionated heparin (UFH) and mechanical prophylaxis (MP). However, this treatment comes with an increased risk of hemorrhage; the odds ratio for hemorrhage has been reported to be as high as 6.38 [95% confidence interval (CI): 0.58-69.91] when compared with placebo [4]. Postoperative hemorrhage following craniotomy, especially in the posterior fossa, can be catastrophic for patients [2,11].…”
Section: Introductionmentioning
confidence: 99%